Study of Shipboard Power Distribution System: Review on an Aplication of AC Zonal Distribution - Danang Cahyagi; Eddy S. Koenhardono (Institut Teknologi Sepuluh Nopember, 2018)
The shipboard power distribution system has been developed in order to make it more efficient. AC zonal distribution system is one of the options in order to achieve the objection. This study aims to observe the shipboard application with AC zonal distribution system. The distribution system is modeled, simulated, analyzed, and compared with conventional system. Based on simulation, the AC zonal distribution system provide higher reliability, better power continuity, and more stable power generation. Therefore, development of the zonal distribution system continues to bring succeed in every mission. However, the system has several challenges for future work such as more complex transmission system, higher voltage drops, and the tendency to have instability power distribution when one generator fails.